Advanced predictive modelling applied to the chemical stabilisation of soft soils. Issue 6 (11th December 2020) - Correia, António A. S.; Lopes, Luis; Reis, Marco S.
Abstract : Over recent decades the chemical stabilisation technique has been applied with success in many transportation geotechnics applications. However, the development of chemical stabilisation techniques requires the efficient extraction of critical information from experimental trials and their integration in accurate and robust predictive modelling frameworks to be used by practitioners. This is the case for cement-based stabilisation technology for soft soils, where binder quantity ( b ), water content ( w ) and the curing time ( t ), play a key role in the final soil's geomechanical properties, namely the unconfined compressive strength ( q u ) and the undrained secant Young's modulus at 50% of q u ( E u50 ). This work presents an integrated optimal experimental design and advanced modelling approach that minimises the experimental costs and derives generalisable models ( q u against b and E u50 against b ) for the conditions of interest ( w and t ). The proposed framework is instrumental for engineers to define the necessary processing conditions to apply when stabilising a given soil and is very efficient with respect to the experimental effort and costs required.